Improving Datapath Testability by Modifying Controller Specification. Issue 2 (2002) - Flottes, M. L.; Rouzeyre, B.; Volpe, L.
Abstract : A digital circuit includes two main parts: a controller and a datapath. After connection of these two parts, both are subject to a sharp fall in testability due to the lack of controllability and observability at the interface. In this paper, we propose a method for specifying the control part in order to restore the testability of the datapath to a level close to the initial one, in other words its testability before connection. This testability driven specification affects the next state logic as well as the decoder part of the controller but does not make use of any scan-based element. Based on the finite automata theory and on results of a testability analysis performed on the datapath, the proposed method entails very little area penalty.